Analisis Kemaslahatan Pada Putusan MA Tentang Wasiat Waji>Bah Dalam Pemberian Hak Waris Bagi Non Muslim (Studi Analisis Pada Putusan MA No. 51.K/AG/1999) - Chairunnisa, Faradilla; Supriyanto, Agus (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
The objectives of this study are as follows, (1) To find out the legal position wasiat waji>bahin the distribution of inheritance for non-Muslims; (2) To find out the reasons behind the decisionMahkamah Agung in deciding inheritance rights for non-Muslims in the form wasiat waji>bah;and (3) To analyze the benefit of the Verdict Mah-kamah Agung No.51.K/AG/1999. The method usedin this research is the Inductive method, which is in the form of drawing general conclusions or abasic knowledge of specific matters. That is, from the existing facts a conclusion can be drawn. Thistype of research is library research or library research. This research is descriptive and maslahahanalysis. The conclusion of this study, first, the legal position of wills in giving inheritance for non-Muslims in KHI does not mention that a person is prevented from becoming an heir due to religiousdifferences. Non-Muslim heirs in Islamic law are located outside the heirs who have the right toreceive an inheritance, because religious differences become an obstacle to obtaining inheritancerights. The Hanafiyah Ulama viewed the will to non-Muslim heirs as valid and the jurists agreed thatthe testament to the Muslim ghair ahl al-dzimmah was permissible. Therefore, granting inheritancerights to non-Muslims in the form of a compulsory will is legal because religious differences do notbecome a barrier to the validity of a will. Second, in its decision, the Panel of Judges gave reasons forgranting inheritance rights to non-Muslims through a mandatory will without questioning the religionof the heirs by stating that non-Muslim heirs have the right to receive inheritance with the sameproportion as religious heirs. Islam from the inheritance left by the heirs. Third, the researcher foundthat there was a problem in the Supreme Court decision no. 51.K / AG / 1999. First, the existence ofmas} lah} ah according to syara ‘belongs to al-Mas} lah} ah al-Mursalah. Second, the level of needbased on the priority of use is included in the Maslahah Daruriyat aimed at maintaining the purposesof Islamic law (Maqasid al-Syari’ah) and avoiding damage. Third, the content of the maslahah orwhich priority should take precedence is included in the Maslahah al-Ammah. Fourth, change an as afixed or changing limitation, including in Maslahah al-Mutaghayyirah and Fifth, there is a principleof Justice.